1971
DOI: 10.1055/s-0028-1094121
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Thyrocalcitonin (Calcitonin) of the Cyclic AMP-Mediated Stimulation of Thymocyte Proliferation by Epinephrine

Abstract: important mitogcnic action of parathyroid hormone, it is proposed that thyrocalcitonin (calcitonin) may bc a general regulator of cyclic AMP-controlled cell proliferation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In mixed cell preparations from rat thymus, salmon calcitonin inhibited apparently cAMP-mediated stimulation by epinephrine of thymocyte proliferation (19). On the other hand, the calcitonin did not affect [3H]thymidine incorporation into 8866 cells (not shown).…”
Section: Methodsmentioning
confidence: 91%
“…In mixed cell preparations from rat thymus, salmon calcitonin inhibited apparently cAMP-mediated stimulation by epinephrine of thymocyte proliferation (19). On the other hand, the calcitonin did not affect [3H]thymidine incorporation into 8866 cells (not shown).…”
Section: Methodsmentioning
confidence: 91%
“…In 1973, Harrell, Binderman and Rodan confirmed these findings in isolated bone cells (Harrell, Binderman & Rodan, 1973). Other indirect evidence suggests that the cytoplasmic calcium activity is depressed by calcitonin (Nisket & Nordin, 1968;MacManus & Whitfield, 1970;Whitfield, MacManus & Gillan, 1971). Both reports concluded that calcitonin may act by inhibiting the active transport mechanism responsible for the cellular extrusion of calcium or by decreasing the concentration of intracellular calcium available for transport.…”
mentioning
confidence: 86%
“…This localization of the initiating reactions is based on the fact that exogenous cyclic AMP maximally stimulates DNA synthesis and cell proliferation without entering the cell (6,7,9,10). Cyclic AMP (both endogenous and exogenous) may stimulate the activation site to produce intermediate compounds which enter the cell and start the calciuminsensitive DNA-synthetic reaction and the calcium-sensitive mitogenic process (Fig.…”
Section: Discussion the Additional Cyclic Ampmentioning
confidence: 99%
“…Since PGE1, like other cyclic AMP elevators, and cyclic AMP itself (6,(8)(9)(10)(11)13), rapidly (within 1 hr) stimulates the initiation of DNA synthesis (Table I ) , cyclic GMP and its mediator, calcium, may influence the prostaglandin mitogenic action by affecting this initial process. Despite the different elevations of the intracellular cyclic AMP level caused by 0.5 and 5.0 p g of PGEJml, DNA synthesis was equally stimulated, and was completely unaffected by calcium (Table I).…”
mentioning
confidence: 99%
See 1 more Smart Citation